2004
DOI: 10.3139/217.1802
|View full text |Cite
|
Sign up to set email alerts
|

Impact Strength of β-Nucleated Polypropylene

Abstract: Structural transformations of semicrystalline polymers form an important field of current scientific research. The preparation of controlled supermolecular structure may lead to significant improvements in mechanical, thermal and optical properties. As for isotactic polypropylene (iPP), its properties essentially depend on its crystalline phase composition, which is due to polymorphism of iPP. Thus, the aim of this work is to analyze the influence of the β-phase content in polypropylene and of its spatial arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…The first resin, named HPP, was a homopolymer without nucleating agent. The second resin, named NPP, had sodium benzoate as nucleating agent in the concentration up to the critical concentration at which the β-form content reaches the saturation level 19,20,39 . Properties of both resins are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first resin, named HPP, was a homopolymer without nucleating agent. The second resin, named NPP, had sodium benzoate as nucleating agent in the concentration up to the critical concentration at which the β-form content reaches the saturation level 19,20,39 . Properties of both resins are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature [17][18][19][20][21] was revealed the promising mechanical properties of β-form in i-PP articles and it was also exposed that when special crystallization procedures are used or, in particular, specific nucleators as N,N'-dicyclohexylnaphthalene-2,6-dicarboxamide and sodium benzoate are added, the β-form can become as predominant crystalline form in common i-PP articles. Dong and cowokers 17 demonstrated that the sodium benzoate shows apparently versatile nucleating characteristic on the crystallization behavior of i-PP and that this nucleating activity is highly dependent on processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, flexural properties are not usually described in studies dealing with the properties of b-iPP. Our previous work [12], which focused on the specific b-nucleation effect of the nucleator based on N, N'-dicyclohexylnaphtalene-2,6-dicarboxamide (NU100), has revealed that the concentration of 0.03 wt.% of the nucleator can be rated as a "boundary value", since the application of this amount leads to rapid increase of b-phase content and to the achievement of the maximum impact strength. Thus, the aim of the present study is to prove, on both flexural and tensile properties, enhanced ductility of the material with this particular nucleator concentration.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] However, only a few papers deal with the microhardness of the skin and the core structure in correlation with the tensile properties.…”
Section: Introductionmentioning
confidence: 99%